THE EFFECT OF CYBER-RELIGION AND THE UNDERSTANDING OF ISLAMIC VALUES IN DEFINING HIJRAH - Muhammad Labib (Tadibia Islamika, 2021)
This research is motivated by the hypothesis that the meaning of hijrah for students at SMA Negeri 1 Pekalongan is determined by cyber-religion activities and understanding of Islamic religious values. This study aims to analyze the influence of cyber-religion on the meaning of hijrah, the influence of understanding Islamic religious values ​​on the meaning of hijrah, and the effect of cyber-religion activities and understanding of Islamic religious values ​​together on the meaning of hijrah for students of SMA Negeri 1 Pekalongan. The research method used is a quantitative research method. Respondents were 168 students of Class XI SMA Negeri 1 Pekalongan using simple random sampling method. This type of research is associative research, because this research intends to determine the causal relationship between two or more variables. Data was collected through questionnaires and school documents. Data analysis used multiple regression analysis. The results showed, 1). Cyber-religion activities have a significant effect on the meaning of hijrah for students at SMA Negeri 1 Pekalongan, 2). The understanding of Islamic religious values ​​has a significant effect on the meaning of hijrah for students at SMA Negeri 1 Pekalongan, 3). Cyber-religion activities and understanding of Islamic religious values ​​together have a positive effect on the meaning of hijrah for students at SMA Negeri 1 Pekalongan. Based on the analysis of the determinants, the variables of cyber-religion activity and understanding of Islamic religious values ​​were able to explain the variable meaning of hijrah students at SMA Negeri 1 Pekalongan by 0.259 (R2 = 0.259). While the remaining 0.741 is influenced by other variables, outside the variables in the study. The results showed that the variable cyber-religion activity more dominantly influenced the meaning of hijrah than the variable understanding of Islamic religious values. This is evident from the results of the t-test showing that the cyber-religion activity variable is 6.702, while understanding the value of Islam is 2.652.